Menabur Kebiasaan: Propaganda Gerakan Menabung Jepang (1941-1945) - Mufidha Brilian Irianti (Universitas Gadjah Mada, 2014)
Japan colonialism during World War II brought signifcant impact for Indonesia. Aside from political and social impacts, it has affected daily life. Japanese occupation was meant to recruit human resources from the region on behalf of the Pacifc War. Japan made efforts to capture the attention and cooperation of locals. Japanese propaganda used a variety of media to send the messages. One such propaganda consisted to persuade people to save in formal institutions. In order to reach people of all backgrounds, military government used a variety of mass media such as newspapers, magazines, movies, and radio as well as a kind of theatrical art and singing. The concern of the paper is to describe the strategies of Japanese savings propaganda. Exploring how government used media to persuade people to make saving accounts in modern fnancial institution.